Observe, See, Listen and Hear: a methodology to qualify the educational practice in day care centers - Ariosi, Cinthia Magda Fernandes [UNESP]; Manfre, Viviane Barrozo [UNESP] (Univ Nove De Julho-uninove, 2024)
Observe, see, listen and hear are actions that comprise the educational practice in the day care center, as they allow the educator to know her children in a deeper way and thus offer the best educational opportunities. With the aim of contributing to the improvement of the pedagogical development of teachers who work in very early childhood, based on reflections on the observation of children, this text was developed from a bibliographical research on reference materials. Observation must be learned, since it is an action that requires preparation. From the analysis, discussion and reflection of the data obtained by observing the children, it is possible to carry out continuing education actions for daycare professionals.
Keywords: nursery; child education; continuing training; observation; listening pedagogy